1997
DOI: 10.1074/jbc.272.32.19672
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Characterization of the Novel Proprotein Convertase PC7

Abstract: Biochemical and enzymatic characterization of the novel proprotein convertase rat PC7 (rPC7) was carried out using vaccinia virus recombinants overexpressed in mammalian BSC40 cells. Pro-PC7 is synthesized as a glycosylated zymogen (101 kDa) and processed into mature rPC7 (89 kDa) in the endoplasmic reticulum. No endogenously produced soluble forms of this membrane-anchored protein were detected. A deletion mutant (65 kDa), truncated well beyond the expected Cterminal boundary of the P-domain, produced soluble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
91
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 85 publications
(98 citation statements)
references
References 52 publications
7
91
0
Order By: Relevance
“…The 12-mer peptides were incubated in vitro overnight with 2 units of purified PCs [2 pmol amino methyl coumarin (AMC) released per minute from the peptide Pyr-RTKR-MCA) (43)], in 2 mM CaCl 2 and 25 mM Tris-Mes, pH 7.5, in a volume of 100 l. The products were separated by RP-HPLC on a Varian C 18 column (5 m, 100 Å, 4.5 ϫ 250 mm), and MS confirmed that cleavage took place exclusively after Arg 296 . HEK293 cells were grown in DMEM containing 10% heat-inactivated FCS (Canadian Life Technologies) at 37°C in 5% CO2.…”
Section: Pcr Genotyping Of Embryos and Micementioning
confidence: 99%
“…The 12-mer peptides were incubated in vitro overnight with 2 units of purified PCs [2 pmol amino methyl coumarin (AMC) released per minute from the peptide Pyr-RTKR-MCA) (43)], in 2 mM CaCl 2 and 25 mM Tris-Mes, pH 7.5, in a volume of 100 l. The products were separated by RP-HPLC on a Varian C 18 column (5 m, 100 Å, 4.5 ϫ 250 mm), and MS confirmed that cleavage took place exclusively after Arg 296 . HEK293 cells were grown in DMEM containing 10% heat-inactivated FCS (Canadian Life Technologies) at 37°C in 5% CO2.…”
Section: Pcr Genotyping Of Embryos and Micementioning
confidence: 99%
“…N-terminal radiosequencing (26,30) was carried out on SDS-PAGE-purified immunoprecipitates. The C-terminally flagged 72-kDa [pro-BACE F ] FG , labeled with [ 3 H]Leu and produced in the presence of ␣ 1 -PDX, had a Leu at positions 3, 7, 9, and 13 (not shown).…”
Section: Biosynthesis and Processing Of Bace-mentioning
confidence: 99%
“…1, right panel), showing that the unglycosylated pro-LPC detected in these transfections is the result of translation initiation at the second ATG codon. This methionine is located 35 amino acids carboxyl-terminal of the first methionine, two amino acids aminoterminal of the major signal peptide cleavage site, and five amino acids amino-terminal of the minor signal peptide cleavage site (11). Translation initiation at this ATG codon will result in the biosynthesis of a protein without a functional signal peptide.…”
Section: Methodsmentioning
confidence: 99%
“…It is widely expressed, both during embryogenesis and adult life (8,9), and has a substrate specificity similar but not identical to that of furin (10,11). LPC is the least conserved family member, and phylogenetic analysis indicates that LPC is more related to kexin in yeast than to any other mammalian PC (12,13).…”
mentioning
confidence: 99%